Proper Predation and Density-Dependent Mortality Control Chaotic Dynamics: Conclusion Drawn from a Leslie-Gower Type Tritrophic Food Chain Model - Sardar, Purnendu; Mukherjee, Chandrani; Biswas, Santosh; Das, Krishna Pada (Journal of Applied Nonlinear Dynamics, 2026)
It has been investigated how proper predation and density dependent mortality affect chaotic dynamics in ecosystems using the Leslie-Gower type tritrophic food chain model. The model demonstrates how proper predation, in which predators choose lesser prey, can regulate population dynamics and avert food chain disruption. The system can also be stabilised by density-dependent mortality, which occurs when the mortality rate of prey rises as population density does. The model also shows that interactions between populations of predators and prey determine how effective these control mechanisms are. Proper predation and density-dependent mortality have a stronger effect on stability when the interaction is moderate, but their impact is lessened when the interaction is robust. The management of ecosystems and conservation efforts will be significantly impacted by these discoveries. We can contribute to the maintenance of stable population dynamics and avert population collapse by encouraging appropriate predation and density-dependent mortality in ecosystems. This emphasises how crucial it is to take into account the intricate relationships between predator and prey populations when managing and conserving ecosystems.